Navigating the complexity of calf injuries in athletes: a review of MRI findings. (June 2022) - Sergot, Leon; Leaper, Oliver; Rolls, Andrew; Williams, Jonathan; Chakraverty, Robin; Chakraverty, Julian
The calf muscle group is a common area for injury within the professional athlete population. Anatomical and biomechanical differences between the different component muscles vary their individual predispositions to and patterns of injury. However, there is a common unifying factor: injuries involving tendinous components have greater clinical implications with regards to rehabilitation, potential intervention, length of time to return to play, and re-injury rates. As such, accurate understanding of the underlying anatomy and subsequent interpretation of the injury patterns carry significant clinical ramifications. Ultrasound is a useful tool but has limitations, particularly when assessing soleus. As such, magnetic resonance imaging remains the workhorse in calf injury investigation.